1998
DOI: 10.1097/00005768-199811000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in urban white, African-American, and Mexican-American women

Abstract: These results indicate that public health efforts to increase physical activity in women should be focused on women of color, women over 40, and women without a college degree. More attention to predictors of physical activity that are specific to race or ethnicity may improve intervention program design and implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
2
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 31 publications
9
55
2
6
Order By: Relevance
“…Some studies show a modest positive relationship between income and LTPA (20,26), but income was unrelated to physical activity in several other studies (27)(28)(29). The association between occupation and physical activity also remains unclear (26,30).…”
Section: Resultsmentioning
confidence: 98%
“…Some studies show a modest positive relationship between income and LTPA (20,26), but income was unrelated to physical activity in several other studies (27)(28)(29). The association between occupation and physical activity also remains unclear (26,30).…”
Section: Resultsmentioning
confidence: 98%
“…The social environment has been identified as a strong predictor of physical activity while marital status and occupation have been shown to be related to physical activity. [37][38][39] Most of these women were employed (24 out of 35 Black women and 27 out of 39 White women). Of those employed, 12 out of 24 Black women and 14 of the 27 White women were in professional jobs (physician, pharmacist, nurse, dietician, or research program coordinator), making it less likely that occupation played a major role in ethnic differences in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In addition, several studies have found that Black subjects have lower physical activity and higher prevalence of obesity than White subjects. [4][5][6][7][8][9][10][11] Although it is known that social and cultural factors may affect participation in physical activity, little is known concerning potential physiological factors that might influence the lower physical activity found in Black subjects.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is unclear how many of the racial/ethnic differences in physical activity can be explained by socioeconomic variables such as level of education. [9][10][11][12][13] Second, few studies have included representative samples of American Indian/Alaskan Native women. Third, little research is published on women 40 years and older, who are at increased risk of both physical inactivity and chronic diseases.…”
mentioning
confidence: 99%